An Empirical Investigation of EFL Teachers’ Digital Competences and Its Pedagogical Application - Salsabila, Fera; Mirizon, Soni; Vianty, Machdalena (JOLLT Journal of Languages and Language Teaching, 2025)
In an increasingly digital age, the integration of technology into education has become imperative, particularly in the domain of English language teaching. This study focuses on evaluating the digital competence of Junior high schools English teachers, with a primary emphasis on their proficiency and efficacy in utilizing digital tools within their teaching practices. Utilizing a qualitative research methodology, the study employed a combination of questionnaires and semi-structured interviews to assess teachers' digital skills. The study explored six core competence areas as delineated by the Digital Competence Framework for Educators (DigCompEdu), which include professional engagement, digital resources, teaching and learning, assessment, empowering learners, and facilitating learners' digital competence. The analysis revealed that English teachers demonstrate commendable digital competence, predominantly classified as "Integrators" in five of the six DigCompEdu domains, and as "Experts" in the Empowering Learners domain. More experienced teachers showcase superior skills in personalizing learning and utilizing diverse digital tools like WhatsApp, Google Forms, Canva, and TikTok. Conversely, less experienced teachers primarily rely on conventional tools, highlighting the need for effective mentorship and structured guidance. The findings have significant implications for school leaders, policymakers, and teacher education institutions, advocating for mentorship systems, enhanced professional development programs that integrate pedagogical strategies, and practical training in adaptive digital resource development. Ultimately, this study emphasizes the necessity of ongoing support to foster sustainable digital competence in educators, contributing to the global discourse on digital pedagogy in 21st-century education.